2018
DOI: 10.1017/s0022215117002481
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and mean platelet volume in patients with tinnitus

Abstract: The results suggest that a prothrombotic condition might play a role in the pathophysiology of tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
19
1
Order By: Relevance
“…(1) Male or female, ages 18-60 (2) Unilateral or bilateral subjective tinnitus (3) History of severe subjective tinnitus for at least 1 year (4) Severe tinnitus according to the Tinnitus Handicap Inventory (THI) questionnaire (more than 38 points) (5) undetectable etiology of tinnitus in an otolaryngology examination (6) No treatment received within the last 6 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Male or female, ages 18-60 (2) Unilateral or bilateral subjective tinnitus (3) History of severe subjective tinnitus for at least 1 year (4) Severe tinnitus according to the Tinnitus Handicap Inventory (THI) questionnaire (more than 38 points) (5) undetectable etiology of tinnitus in an otolaryngology examination (6) No treatment received within the last 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…The sound perceived without an external stimulus is considered to be caused by abnormal neural activity along the hearing path from the cochlear apparatus to the auditory cortex. 6 Complementary and alternative medicine treatments are often used to treat tinnitus, and one of the most frequently used options is acupuncture. 7 Acupuncture therapy in patients who have tinnitus has been described extensively in books 8 ; however, scientific literature still lacks studies that support its therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The mean PLR values were 138.24 ± 50.83 in the patient group and 127.39 ± 45.31 in the control group. There Ulusoy et al [16] showed that MPV values were significantly higher in tinnitus patients than the control group. MPV values were studied also in sudden sensorineural hearing loss (SSHL) patients and results were controversial like tinnitus patients.…”
Section: Discussionmentioning
confidence: 94%
“…PLR has also been used frequently as an indicator of inflammation in many studies. Ulusoy et al (15) studied PLR in tinnitus patients and they found no difference when compared to the control group. On the other hand, Atan et al (24) claimed that PLR can be used as diagnostic parameter for pediatric chronic serous otitis media.…”
Section: Discussionmentioning
confidence: 96%
“…The NLR has been examined in many otolaryngological conditions. Ulusoy et al (15) examined NLR in tinnitus and found no significant difference between tinnitus patients and control group. However, Ozbay et al (16) claimed that NLR could be used as a potential clinical marker in tinnitus patients.…”
Section: Discussionmentioning
confidence: 98%